1988
DOI: 10.1016/0014-5793(88)80005-x
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of adenosine on two types of cAMP‐induced gene expression in Dictyostelium indicate the involvement of at least two different intracellular pathways for the transduction of cAMP signals

Abstract: Adenosine promotes the CAMP-induced increase of mRNAs, probed with the cDNAs Dl 1 and D14, which are preferentially expressed in prestalk cells, while it inhibits CAMP-induced prespore gene expression. Half-maximal inhibition of prespore gene expression occurs at about 300 PM, while prestalk stimulation by adenosine occurs at about lOO-fold lower concentrations and requires the presence of CAMP. These results indicate that adenosine interferes with the transduction of CAMP to gene expression and suggest the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We found that adenosine had no effect on the accumulation of any of the three developmentally regulated transcripts in monolayers of V12-M2 (data not shown). This result was surprising, since Schaap and coworkers recently reported that adenosine inhibited D19 mRNA accumulation and stimulated D11 mRNA accumulation in cyclic AMP-pulsed suspensions of NC4 cells [37]. However, since high concentrations of cyclic AMP have been shown to counteract the effects of adenosine [37, 431, our negative results might be explained by the high concentration of cyclic AMP that is required for stalk cell formation in the monolayers.…”
Section: The Effects Of Adenosine On Gene Expressionmentioning
confidence: 63%
“…We found that adenosine had no effect on the accumulation of any of the three developmentally regulated transcripts in monolayers of V12-M2 (data not shown). This result was surprising, since Schaap and coworkers recently reported that adenosine inhibited D19 mRNA accumulation and stimulated D11 mRNA accumulation in cyclic AMP-pulsed suspensions of NC4 cells [37]. However, since high concentrations of cyclic AMP have been shown to counteract the effects of adenosine [37, 431, our negative results might be explained by the high concentration of cyclic AMP that is required for stalk cell formation in the monolayers.…”
Section: The Effects Of Adenosine On Gene Expressionmentioning
confidence: 63%
“…While positional information may not be essential in this initial patterning of prestalk A cells, it presumably is important in maintaining the pattern and in controlling Dd-ras and Dd63 expression later in development (this report ;Schaap 1986;Wang et al 1986Wang et al , 1988aWilliams et al 1987Williams et al , 1989. The stabilization and maintenance of this pattern would require the interplay of cAMP, DIF, adenosine, NHJ, and possibly other morphogens (Nestle and Sussman 1972;Williams et al 1984;Schaap 1986;Schaap and Wang 1986;Spek et al 1988;Wang et al 1988). It is possible that the cell sorting mechanism combined with the preferential expression of appropriate gene products initially establishes gradients that may be required to stabilize the spatial pattern established in the tipped aggregate.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, it is possible that the cell cycle controls the initial, apparently random patterning of Dd-ras-and D(i63-expressing cells. Although all cells within the developing aggregate during aggregation receive the cAMP signal, they may respond differently due to differences in the cAMP-signaling pathways in the two cell types (see Spek et al 1988;Ginsberg and Kimmel 1989). These cells may then sort, possibly in response to cAMP signals, with the Ddras-expressing prestalk cells migrating toward the tip.…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently reported that the application of adenosine to pseudoplasmodia decreased the number of prespore cells, while addition of adenosine deaminase had the opposite effect ). In addition, adenosine stimulated prestalk cell enriched gene expression and inhibited prespore cell specific gene expression in shaken suspensions of NC-4 (Spek et al 1988). This data is consistent with the idea that adenosine stimulates the stalk cell pathway of differentiation at the expense of the prespore cell pathway.…”
Section: Adenosinementioning
confidence: 97%